Doppler ultrasonography imaging of recurrent choroidal detachment following facotrabeculectomy – a case report - Obuchowska, Iwona; Ustymowicz, Andrzej; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
The authors describe a case of 78-year-old women, who underwent uneventful facotrabeculectomy with posterior chamber intraocular lens implantation and experienced late and recurrent choroidal detachment. Color Doppler imaging of the ophthalmic artery, central retinal artery, short posterior cilliary arteries and vessels on surface of choroidal detachment was carried out. The parameters of blood flow in all arteries were normal. Spectrum of flow in the vessels on surface of choroidal detachment was similar to this of central retinal artery. Color Doppler ultrasonography is useful diagnostic method in evaluation of vascular bed in eye with choroidal detachment.